(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The focus of the article is on school meal programs that are common throughout the world and are implemented to promote students’ healthy eating habits and bring added value to their learning outcomes. In recent years there has been increasing emphasis on the possibility of improving school meals by including locally grown products, thus contributing to the development of local economic systems. This model has acquired the name "Farm to School" in practice of some countries and, according to its supporters, emphasizes public procurement of locally grown food as a key market opportunity for farmers. The article has been prepared within the BSR Food Coalition project (funded by Interreg Baltic Sea Region Program, contract #S002). The project seeks to create the conditions for the emergence of the "From farm to school" model in the Baltic States. The study presented in the article aims at disclosing the conditions and opportunities for the promotion and use of foods produced by local farmers in general education schools in Klaipeda region, Lithuania as well as at defining necessary educational efforts to increase healthy nutrition, develop general health habits, and agricultural and food system literacy within general education schools and their communities. To achieve the aim the surveys with project target groups (school administration, students and their parents) have been carried out in Klaipeda region. The objectives of the survey were to gather data on target groups’ perceptions of local school food procurement and to disclose their opinion, needs and expectations related to model development. The findings of the study would be helpful for designing the further steps of collaboration between schools and local farmers in Klaipeda region. .